RELEVANSI PERAN TRIPUSAT PENDIDIKAN KI HAJAR DEWANTARA DENGAN PERSPEKTIF AL-QUR’AN - Lutfiyah, Siti Khumairotul; Thobroni, Ahmad Yusam (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2024)
One of the successes of the process of forming process is influenced by the educational environment. The existence of A good environment is expected to shape good character. Conversely Conversely, a bad educational environment has the potential to shape the character of children who are not good either. The educational environment called the tripartite education by Ki Hajar Dewantara includes the family, school and community. This article aims to find the relevance of the role of Ki Hajar Dewantara's tripartite education with a Qur'anic perspective. This type of research is a literature approach (tafsir maudhu'i). The results found that the role of Ki Hajar Dewantara's tripartite education related to the family environment is relevant to QS. Luqman: 13-19 where this environment as forming the foundation of the child's personality; the school environment is relevant to QS. Al-Jumu'ah: 2 where this environment is a place to get knowledge and teaching; and the community environment is relevant to QS. Ali Imran: 104 where this environment is a place to practice and shape children's character. Nonetheless, the success of character building requires not only the realization of the role of the three centers of education, it is also necessary to have a synergy from the three of them